Semi-invariants of low-dimensional Lie algebras. Issue 5 (4th May 2021) - Alvarez, M. A.; Salgado, G.
Abstract: The aim of this work is to explicitly compute the semi-invariants of low-dimensional Lie algebras by reducing the amount of work, i.e., we can prove that almost every irreducible Lie algebra g, of dimension less than or equal to 5, satisfies the following: It is either a contact Lie algebra or there exists a torus T ⊂ Der ( g ) such that T   ⋉ g is a contact Lie algebra. Therefore, the semi-invariants found by using the contact structure are the same found by using the Frobenius structure.